A Leaf‐Inspired Luminescent Solar Concentrator for Energy‐Efficient Continuous‐Flow Photochemistry. (22nd December 2016) - Cambié, Dario; Zhao, Fang; Hessel, Volker; Debije, Michael G.; Noël, Timothy
Abstract: The use of solar light to promote chemical reactions holds significant potential with regard to sustainable energy solutions. While the number of visible light‐induced transformations has increased significantly, the use of abundant solar light has been extremely limited. We report a leaf‐inspired photomicroreactor that constitutes a merger between luminescent solar concentrators (LSCs) and flow photochemistry to enable green and efficient reactions powered by solar irradiation. This device based on fluorescent dye‐doped polydimethylsiloxane collects sunlight, focuses the energy to a narrow wavelength region, and then transports that energy to embedded microchannels where the flowing reactants are converted.